Eosinophilic granulocytes as a potential prognostic marker for cancer progression and therapeutic response in malignant melanoma - Brand, Corsin Linard; Hunger, Robert Emil; Seyed Jafari, Seyed Morteza (Frontiers in Oncology, 2024)
The importance of eosinophilic granulocytes in cancer has been widely discussed in recent years. The current study reviews the evidence on the role of eosinophilic granulocytes in melanoma as a prognostic marker for cancer progression and the efficacy of treatment with modern immune checkpoint inhibitors. A total of 33 human clinical studies were included in the review, with heterogeneous data due to differences in patients populations, study design and inclusion of small study groups. However, 28 of the 33 studies suggested that eosinophilic granulocytes could be used as a prognostic biomarker for outcome and/or potential response to systemic treatment and/or occurrence of adverse events in melanoma patients. Nevertheless, the exact role of eosinophils remains to be elucidated. Further prospective, larger and better controlled studies are warranted to clarify the significance of eosinophilic granulocytes in patients with melanoma, in more details.